The Uptake and Distribution of 15N enriched Nitrate by three Rootstock Cultivars grafted to Chenin blanc - Conradie, W. J. (South African Journal of Enology and Viticulture, 2017)
The uptake and distribution of nitrogen by the rootstocks 99R, 101-14 Mgt and 140 Ruggeri grafted to Chenin blanc in sand culture, were determined using 15N enriched potassium nitrate. The K15N03 was applied at the end of rapid shoot growth and the vines were sampled at veraison. Although vines grafted on 99R showed less aerial- and root growth than those ~n 101-14 Mgt and 140 Ruggeri, nitrogen was absorbed equally well by all three rootstocks. The distribution of newly absorbed nitrogen could be accurately determined by means of 15N, and at veraison more than half of newly absorbed N was found in the leaves and shoots, and about 15% in the bunches. It was clear that nitrogen which accumulated in the bunches during the period of investigation, was derived primarily from previously assimilated N in the roots and mature wood.